Comment on: "Microtexture and U–Pb geochronology of detrital zircon grains in the Chachalacas beach, Veracruz State, Gulf of Mexico" by Armstrong‐Altrin, J. S., Ramos‐Vázquez, M. A., Hermenegildo‐Ruiz, N. Y., and Madhavaraju, J. (2020). Geological Journal. Issue 3 (12th March 2022) - Ramírez‐Fernández, Juan Alonso; Jenchen, Uwe; Alemán‐Gallardo, Eduardo Alejandro; Casas‐Peña, Juan Moisés; Leal‐Cuellar, Víctor Alejandro
Abstract : Considering the U–Pb ages of detrital zircons grains contained in Holocene sands from the Chachalacas beach as reported by Armstrong‐Altrin, Ramos‐Vázquez, Hermenegildo‐Ruiz, and Madhavaraju (2020) it is possible to track a wide‐ranging record of the most important magmatic and tectonothermal events preserved along NE to SE of Mexico. These zircon‐forming events include those responsible for the development of its Proterozoic basement, the Palaeozoic and Mesozoic magmatic arcs, as well as the Cenozoic arc and intraplate magmatism. The proposed sources for the studied zircon crystals are Oaxaquia, Maya Block, the Peregrina‐Mochonian arc, the Tamatán Group of the Ciudad Victoria Block, the Nazas Arc, the Cretaceous Mexican Arc, the foreland basins of the Sierra Madre Oriental, the Eastern Alkaline Province, and the Trans‐Mexican Volcanic Belt. Abstract : The analysis of detrital zircon crystals contained in recent sediments from the Chachalacas beach in the Gulf of Mexico Western margin, offers a wide‐ranging record of the most important magmatic and tectonothermal events that have occurred along NE to SE of Mexico. These events were responsible for the development of its Proterozoic basement, the Palaeozoic and Mesozoic magmatic arcs, as well as the Cenozoic arc and intraplate magmatism.